The Effects of Executive, Firm, and Board Characteristics on Executive Exit - Becker-Blease,John (Financial Review, 2016)
We estimate a hazard model of the probability of top corporate executives exiting their firms over the period 1996–2010. Our main findings are that: (1) female executives have greater likelihoods of exit than males, (2) the likelihood of exit increases with the independence of the board and decreases with the fraction of the board that is female and the average age of board members, and (3) a higher percentage of independent directors on the board lowers the probability of exit more for females than for males. Further, controlling for exit risk reduces the well-documented compensation differential between men and women.
Keywords: Finance